Lemmus lemmus subsp. chernovi Spitsyn, Bolotov & Kondakov 2021, ssp. nov. ... - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Lemmus lemmus chernovi Spitsyn, Bolotov & Kondakov ssp. nov. Figs 6A, 7 A-C, 7G-H, 7K-L, Table 7 Common name: Novaya Zemlya Lemming Holotype: Male RMBH Lem 005: type locality: Russia, Novaya Zemlya, Southern Island, near Malye Karmakuly Polar Station, 72.3822°N, 52.7506°E, altitude 17 m, wet saxifrage- roseroot communities, 23.vii.2015, Spitsyn leg. Paratypes: Russia, Novaya Zemlya, Southern Island: type locality, 27.vii–01.viii.2015, 11 specimens (RMBH Lem001 – Lem004, Lem006, Lem007, Lem011, Lem019, Lem022, Lem023, Lem027), Spitsyn leg.; near Malye Karmakuly Polar Station, 72.3575°N, 52.7799°E, altitude 27 m, dry lichen- moss rocky tundra, 1.viii.2015, 1 specimen (RMBH Lem028), Spitsyn leg.; near Malye Karmakuly Polar Station, 72.3934°N, 52.7566°E, altitude 40 m, dry lichen- moss rocky tundra, 23.vii.2015, 2 specimens (RMBH Lem008, Lem009), Spitsyn leg.; near Malye Karmakuly Polar Station, 72.4058°N, 52.8285°E, altitude 60 m, dry tundra with Dryas octopetala and Astragalus alpinus, 27.vii.2015, 2 ... : Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on pages 105-108, DOI: 10.37828/em.2021.40.8, http://zenodo.org/record/13233031 ...